Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s1478951519000798
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Portuguese dignity question framework for adolescents: ages 10–18

Abstract: ObjectiveDignity therapy (DT) is well established in adult populations, and it is likely that it could benefit younger people. This study aimed to adapt the adult Portuguese DT question framework for adolescents (DT-QF-Adol) (ages 10–18).MethodFive stages were followed: (1) the Portuguese DT-QF for adults was adapted for adolescents with the original author's collaboration, (2) an expert committee provided feedback on the adapted version, (3) an initial consensus version of the DT-QF-Adol was created, (4) expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
0
11
0
1
Order By: Relevance
“…Last but not least -as Psycho-Oncology focuses on all aspects of every individuals' experience with cancer throughout their whole lifespan, from diagnosis to treatment, during the end of life, and after death -DT has, once more, gained new possibilities and clinical and research "wings". It was already adapted to be integrated into care plans for terminally-ill children and adolescents, 13,14 and most recently, adapted to be posthumously used by those grieving and honouring their deceased, providing a means for the bereaved to assuage their grief. 15 In conclusion -looking at the past, the present and most importantly to DT's future -we believe the inner strength DT holds, resides in its capacity to find each patient's personhood beyond patienthood and still conscientious that personhood is soluble in patienthood.…”
Section: Dear Editormentioning
confidence: 99%
“…Last but not least -as Psycho-Oncology focuses on all aspects of every individuals' experience with cancer throughout their whole lifespan, from diagnosis to treatment, during the end of life, and after death -DT has, once more, gained new possibilities and clinical and research "wings". It was already adapted to be integrated into care plans for terminally-ill children and adolescents, 13,14 and most recently, adapted to be posthumously used by those grieving and honouring their deceased, providing a means for the bereaved to assuage their grief. 15 In conclusion -looking at the past, the present and most importantly to DT's future -we believe the inner strength DT holds, resides in its capacity to find each patient's personhood beyond patienthood and still conscientious that personhood is soluble in patienthood.…”
Section: Dear Editormentioning
confidence: 99%
“…Since the publication of our review, Juliao et al [21] have published their work on adapting the DTQP for adolescent's aged 10 to 18 years in Portugal. They have developed an amended DT set of questions which could be used in practice for sick Portuguese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Julião et al reported a revised version of DT for adolescence, positing several metaphors and tasks to make it more developmentally appropriate. 3 Although this adaptation was based on input from a qualified expert panel, it has yet to be implemented. Schuelke and Rubenstein's study: https://www.liebertpub.com/doi/10.1089/ pmr.2020.0015 offers important insights, suggesting that DT, revised to meet the needs of dying children and adolescents, has a place within the pediatric palliative care therapeutic armamentarium.…”
mentioning
confidence: 99%
“…documents of adolescent patients. 3 Sixteen-year-old Miracle Akbar held a party at which she read her generativity document, whereas Shahd Shahroor had her document translated into her family's native tongue of Arabic and took great pride in the document being used for educational purposes. Although perhaps motivated by altruism, her reaction also suggests comfort in knowing her story will be told.…”
mentioning
confidence: 99%